Anónimo mexicano - Crapo, Richley H.; Glass-Coffin, Bonnie, 1957- (Utah State University Press, 2005)
Anonimo Mexicano is the first publication of the full Nahuatl text and English translation of a rare and important Native history of preconquest Mexico. Written circa 1600 by an anonymous Tlaxcaltecan author, it is an epic account of the settling of central Mexico by Nahua peoples from the northern frontier. They developed a sophisticated culture with powerful city states and an agricultural economy, fought great wars, established dynasties, and recorded their history and legends in painted books. The Mexica became the most powerful of these nations until their conquest by the Spanish with the.